Human expeditions : inspired by Bruce Trigger - Costopoulos, Andre, 1968-; Chrisomalis, Stephen, 1974-; Bard, Kathryn A. (University of Toronto Press, 2013)
In its 2007 obituary of Bruce Trigger (1937-2006), the Times of London referred to the Canadian anthropologist and archaeologist as "Canada's leading prehistorian" and "one of the most influential archaeologists of his time." Trained at Yale University and a faculty member at McGill University for more than forty years, he was best known for his History of Archaeological Thought, which the Times called "monumental." Trigger inspired scholars all over the world through his questioning of assumptions and his engagement with social and political causes. Human Expeditions pays tribute to Trigger's immense legacy by bringing together cutting edge work from internationally recognized and emerging researchers inspired by his example. Covering the length and breadth of Trigger's wide-ranging interests -- from Egyptology to the history of archaeological theory to North American aboriginal cultures -- this volume highlights the diversity of his academic work and the magnitude of his impact in many different areas of scholarship."--Publisher's website.